Political Marketing: The Victory of Natasha Devianti as a Newcomer Millennial Candidate for Legislative Members District Bojonegoro 1 of Election 2019 - Mondir, Nabila; Hermanto, Bambang (Universitas Brawijaya, 2020)
This article describes and analyzes the political marketing of Natasha Devianti as a prospective member of the millennial newcomer who has won. Political marketing is needed as a tool or method for candidates and political parties to approach the public. Natasha Devianti won with the highest votes in the internal PDI-P as many as 5,454 votes. Natasha Devianti's Winning Team segmented the entire community in electoral area 1 Bojonegoro. Natasha as a candidate for the legislative members from PDI-P brought the party's platform to attract the public. Natasha's personal characteristics highlight the millennial character as an offroad racer and drag race that has won many championships at the national level. In addition, Natasha carried the name of his father who was the Deputy Regent of Bojonegoro Regency to increase public trust. Natasha Devianti promoted by utilizing print promotion media, online media, and social media. Natasha branding on social media Instagram to attract millennial voters as the main target. Besides that, Natasha also utilizes several online news media such as kumparan.com, gesuri.id, and news.detik.com. Natasha Devianti as a prospective newcomer legislative member utilizes her youth network as a means of political distribution. Cost politics which tends to be high becomes a quite complicated problem in political marketing. Natasha spent political costs reaching 1 billion rupiahs in the 2019 legislative elections.